Media Pembelajaran dalam Pembelajaran Tematik Integratif di Sekolah Dasar - SURYANDARI, YUNITA (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2020)
In general, learning media is a tool for teaching and learning processes or anything that can be used to stimulate students ' minds, feelings, attention and skills so that they can encourage the learning process. Integrative thematic learning is learning that integrates multiple topics into a theme. This integrative thematic learning provides students with direct experience, and requires students to be more involved in providing comprehensive learning and not being separated.This integrative thematic learning also involves the inculcation of spiritual values and social values which are taught together with the provision of general learning materials.It is very important to use and apply the learning media in integrative thematic learning in elementary schools.This is also focused on the age of children who are still in elementary school and, of course, learning will be of great interest for them when using media that can stimulate and motivatethem to learn. By using appropriate learning media, teachers and students are expected to be able to achieve the planned objectives. Especially students are expected to gain meaningful experience in the spiritual, social, knowledge and skills domains. Thus, learning in schools, particularly at the elementary level can be a foundation for students when they go through adult life so that they become successful humans when they grow up.